Karakteristik Kimia - Fisika Tanah Bekas Tambang Semen Yang Ditambah Sekam Padi atau Serbuk Gergaji dan Pertumbuhan Wodyetia bifurcata A.K. Irvine - Slamet Santosa; Muhamad Ruslan Umar; Meirini R. Bakri (Fakultas Teknik, 2020)
The cement industry only takes the top clay and the next layer of soil is left unused. This study was aimed to analyze some of the chemical and physical properties of the ex-mining land of cement which added with rice husks or sawdust and the growth of Wodyetia bifurcata seedlings. A growth medium is made from ex-mining land of cement by the addition of rice husk or sawdust with a different amount of material percentage. All the growth medium contains organic C ranges of 0.56-3.09%, total N ranges of 0.09-0.33%, available P ranges of 8.42-31.16mg/100g, available K ranges of 6.54-16.32mg/100g, and bulk density ranging of 0.24-1.09gcm-3. The seedling height growth of Wodyetia bifurcate about 13.5 - 15.2 cm, the range of stem diameter is 0,71-0,86 cm, the root length about20.2-29.8 cm, the number of leaves is 2.2-2.8, as well as seed quality index ranging of 0.09-0.13. The addition of 50% rice husk (B2) produced organic C, total N, available P and K and bulk density of the ex-mining land of cement and provides the highest growth of Wodyetia bifurcata A.K. Irvine seedlings.